Pediatric National Surgical Quality Improvement Program: Useful for Quality Improvement in Craniosynostosis Surgery?. Issue 3 (May 2016) - Lam, Sandi; Fridley, Jared; Desai, Virendra R.; Srinivasan, Visish M.; Jea, Andrew; Luerssen, Thomas G.; Pan, I-Wen
Abstract : Abstract: The American College of Surgeons and the American Pediatric Surgical Association collaborate to provide pediatric hospitals with multispeciality surgical outcomes data through the Pediatric National Surgical Quality Improvement Program (NSQIP Peds). The authors used this national multicenter database to describe 30-day outcomes from craniosynostosis surgery and identify associations with perioperative events and blood transfusion. Data from NSQIP Peds were used to describe children undergoing craniosynostosis surgery. The authors examined statistical association of clinical risk factors with the defined end point outcomes of perioperative complications and blood transfusion. Five hundred seventy-two surgeries were included. By Common Procedural Terminology codes, 93 identified as single suture synostosis, the remainder as multiple or unknown suture involvement. Location of the affected suture is not captured. Mean surgical time was 196.84 minutes (SD 113.46). Mean length of stay was 4.22 days (SD 5.04). Sixty-seven percent of patients received blood transfusions. 3.15% were other perioperative occurrences, including infection, wound disruption, unplanned reintubation, stroke/hemorrhage, cardiac arrest, seizures, thromboembolism. 2.8% were readmitted; 2.45% underwent reoperation within 30 days. Duration of surgery and length of hospital stay significantly differed in the presence of blood transfusion versus none. On multivariate analysis, duration from anesthesia start to surgery start, duration from surgery end to anesthesia end, and duration of operation were risk factors for blood transfusion. Pediatric NSQIP gives a national overview of 30-day outcome metrics in craniosynostosis surgery. Perioperative adverse event rate was 3.15%. Duration of surgery and duration of anesthesia were significantly associated with blood transfusion. The authors identified opportunities for pediatric NSQIP database improvement.